Analisis Desain Ulang Formulir General Consent di Bagian Pendaftaran Rawat Jalan - Azkiya Salsabilla Setyaputra Salsa; Anton Kristijono; Yuliantisari Retnaningsih (Poltekkes Kemenkes Yogyakarta, 2025)
The use of data items in the outpatient registration general consent form at Nyi Ageng Serang Hospital Kulon Progo is not in accordance with the data items contained in the Decree of the Minister of Health of the Republic of Indonesia Number HK.01.07/MENKES/1423/2022. Regarding Guidelines for Variables and Metadata in the Implementation of Electronic Medical Records The impact of incomplete data is that when there is case of malpractice, the data cannot be used as means of protection for both the hospital and the patient, so it was necessary to redesign the general consent form. The purpose of this research was Identify, analyze, design, and describe the acceptability of redesigning general consent forms from paper to electronic at Nyi Ageng Serang Hospital, Kulon Progo. This research used qualitative descriptive study with a case study approach. This research was conducted in April–May 2023. Respondents in this study were 2 registration officers, 1 IT team, 1 DPJP person, 1 education and training employee, 1 HPK working group team, and 1 head of medical records at Nyi Ageng Serang Hospital Kulon Progo. The results of the identification and analysis show that the anatomical aspects and the contents of the general consent form at Nyi Ageng Serang Kulon Progo General Hospital are not in accordance with the form design standards. When the redesign was carried out, there were changes to the form material, headings, instructions, margins, rules, font and size, way of recording, closing, and completeness of data items. Based on the description of the acceptance of the general consent redesign, the average score of the seven respondents was 81%-100%, so it was included in the